Research of dynamic properties of control system for reversible hydropower supply units with variable rotational speed on hydroelectric pumped storage power plant - Червоненко, Иван Игоревич (Eastern-European Journal of Enterprise Technologies, 2015)
The research of performance and dynamics of a new automatic control system of reversible hydropower supply units in standard operation modes and in the pressure efficiency correction mode was performed. The efficiency of such a system and the possibility of its use for reversible hydraulic turbines of all types of HPSPP, including underground and mine HPSPP was shown. This is determined by the adjustment accuracy of pressure parameters and, therefore, the need to open the guide apparatus, corresponding to optimal efficiency, as well as full compliance with the quality control requirements. It is assumed that the hydropower supply unit, operating with the variable rotational speed, will include an asynchronized generator instead of synchronous one. The effect of pressure setpoint level on the control smoothness and the nature of transients was investigated. It was proved that with a decreasing level of setpoints, transients are virtually eliminated. Based on the stability region obtained, the selection of controller parameters was made. The curves of transients during the turbine operation with synchronous rotational speed and in the efficiency correction mode, during the operation with variable rotational speed were analyzed. It was shown that the value of overspeeds and the number of overshoots during the load drops do not exceed the requirements placed on the quality control of serial hydraulic turbines.